Beyond the Obstruction: A Case of Lung Cancer with Coincidental COPD Diagnosis - Rosi Maulini; Masrul Basyar; Deddy Herman; Yessy Susanty Sabri (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Lung cancer frequently coexists with chronic obstructive pulmonary disease (COPD), particularly among smokers. The presence of both conditions can complicate diagnosis and lead to poorer outcomes. This case report presents a patient with lung cancer and concurrent COPD, highlighting the diagnostic and management challenges. Case presentation: A 60-year-old male presented with a history of smoking, progressive dyspnea, and a recent diagnosis of right lung cancer (T4N3M1c, stage IV B). He also exhibited symptoms suggestive of COPD, such as chronic cough and expectoration. Spirometry confirmed moderate restriction and severe obstruction, consistent with COPD GOLD 3. The patient was managed with both lung cancer treatment and COPD therapy. Conclusion: This case underscores the importance of considering COPD in patients with lung cancer, especially those with a history of smoking. Early diagnosis of both conditions is crucial for optimizing treatment strategies and improving patient outcomes.